Living with aircraft noise: Airport proximity, aviation noise and subjective wellbeing in England. (January 2016) - Lawton, Ricky N.; Fujiwara, Daniel
Highlights: Novel study into the effects of airports on multiple subjective wellbeing metrics. Merges geolocated national population statistics with airport noise measurement maps. Daytime aviation noise negatively impacts on all five subjective wellbeing measures. We find a marginal negative association with additional decibels of aircraft noise. Supports revealed preference evidence of lower market demand with aviation noise. Abstract: Airport expansion is an issue of intense public debate due to the potential impacts on climate change and the quality of life of affected local communities. This paper is the first study to analyse the relationships between airports and multiple subjective wellbeing measures, by merging national-level population statistics with noise measurement maps for seventeen English airports. The presence of daytime aviation noise was found to consistently negatively impact on five subjective wellbeing measures. We found a marginal negative association with every additional decibel of aircraft noise. We found no significant association between wellbeing and living within night-time noise contours or living in close airport proximity. We conclude that living under air traffic flight paths has a negative effect on peoples' overall and momentary wellbeing, equivalent to around half the effect of being a smoker for some wellbeing measures. The subjective wellbeing method findings support wider revealed preference literature showing lower market demand in areas affected by aviation noise.